2016
DOI: 10.1007/s00359-016-1090-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of steady swimming on fish escape performance

Abstract: Escape maneuvers are essential to the survival and fitness of many animals. Escapes are frequently initiated when an animal is already in motion. This may introduce constraints that alter the escape performance. In fish, escape maneuvers and steady, body caudal fin (BCF) swimming are driven by distinct patterns of curvature of the body axis. Pre-existing muscle activity may therefore delay or diminish a response. To quantify the performance consequences of escaping in flow, escape behavior was examined in blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…For attacks from the cranial direction at intermediate flow speeds, more streamlined fish exhibited higher peak accelerations than tallerbodied fish. These results support the potential for ambient flow conditions to affect fast-start escapes (Anwar et al, 2016). Specifically, when fish are oriented with the head into the flow, escapes from cranial attacks could be aided by ambient flow during movement away from a predator.…”
Section: Peak Velocity and Accelerationsupporting
confidence: 67%
See 1 more Smart Citation
“…For attacks from the cranial direction at intermediate flow speeds, more streamlined fish exhibited higher peak accelerations than tallerbodied fish. These results support the potential for ambient flow conditions to affect fast-start escapes (Anwar et al, 2016). Specifically, when fish are oriented with the head into the flow, escapes from cranial attacks could be aided by ambient flow during movement away from a predator.…”
Section: Peak Velocity and Accelerationsupporting
confidence: 67%
“…However, these trials were not designed to evaluate individual performance, or to stimulate the lateral line system, which is the primary source of sensory input for detecting and responding to aquatic predators in fish that employ fast-start escapes (Stewart et al, 2014). Finally, a recent study of bluegill escapes from acoustic-pressure wave stimuli found that escapes made while swimming in flow were less variable, but had lower velocities and accelerations, than escapes made in still water, and that performance was greater for escapes directed downstream versus those directed upstream (Anwar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…angular limits in the visual fields), (ii) the need for high speed to distance the prey from the threat (Domenici et al, 2011b;Soto et al, 2015) and (iii) the presence of a shelter (Shi et al, 2017). Recently, the variability of escape trajectories was found to be reduced when fish were startled while swimming in a flow, such that the escape trajectories were in line with the flow direction, possibly to minimise destabilisation that would occur if fish escaped at an angle to the flow (Anwar et al, 2016).…”
Section: Escape Latencymentioning
confidence: 99%
“…In a study by Fu (2015) , qingbo carp Spinibarbus sinensis exhibited a lower mortality rate when they had been acclimated to a high flow environment compared to those acclimated to still water. In addition, various studies suggest that water flow may reduce the ability of the lateral line to detect perturbations in the water created by attacking predators ( Anwar et al, 2016 ; Feitl et al, 2010 ; Liao, 2006 ), potentially creating selection for individuals with a lower response threshold under high flow conditions. Further studies on how flow impacts predator strike performance and success would aid in understanding the contribution of selection to the distribution of fast-start phenotypes among habitat types.…”
Section: Discussionmentioning
confidence: 99%
“…To maximise the benefits of grouping, schools exhibit plasticity in behavioural traits in response to individual needs and environmental stimuli, particularly in group cohesion, coordination and positional preferences ( Hansen et al, 2015 ; Killen et al, 2012 ; Krause and Ruxton, 2002 ; Sogard and Olla, 1997 ; Ward and Webster, 2016 ; Webster et al, 2007 ). Environmental conditions such as water flow regime can influence behavioural and physiological phenotypes of both solitary and schooling fish ( Anwar et al, 2016 ; Binning et al, 2015 ; Langerhans, 2008 ; Liao, 2007 ; West-Eberhard, 1989 ). Chicoli et al (2014) found that individuals and schools exhibit a greater rate of reaction to a threat under an acute high flow treatment compared to a no-flow treatment.…”
Section: Introductionmentioning
confidence: 99%